Selective Use of Pulmonary Vasodilators in Patients with Fontan Physiology - Thomas Glenn; Nicole Duster; Jerry Dwek; Jose Silva-Sepulveda; Howaida G. El-Said (Journal of Interventional Cardiology, 2022)
Background. Fontan-associated liver disease is a well-known sequela following the Fontan procedure for patients living with single-ventricle heart disease. Pulmonary vasodilators, such as phosphodiesterase type 5 inhibitors, have emerged as a potential therapeutic option for lowering central venous pressures by reducing pulmonary vascular resistance. Method. We performed a single-center retrospective review of Fontan patients who were placed on pulmonary vasodilator therapy with prehemodynamic and posthemodynamic, MR elastography, and histologic assessments. Results. A total of 125 patients with Fontan circulation underwent surveillance with cardiac catheterization during the review period. Fifty-three (42%) patients who did not have increased end-diastolic pressures at the time of cardiac catheterization were started on phosphodiesterase type 5 inhibitor therapy. Nine patients (17%) underwent posttherapy follow-up catheterization. The mean Fontan pressure decreased from 15.4 ± 3.3 mmHg to 13.3 ± 2.5 mmHg (p=0.026), after initiation of pulmonary vasodilatory therapy. There was no change in end-diastolic pressure, transpulmonary gradient, wedge pressure, pulmonary vascular resistance, cardiac index, or saturation. Eleven patients (21%) underwent pretherapy MR elastography testing with posttherapy follow-up MR elastography. We found no improvement in liver stiffness score following the application of pulmonary vasodilators. Three patients underwent pretherapy and posttherapy liver biopsies, with variable histological changes observed within the hepatic parenchyma. Conclusions. These data demonstrate indeterminate results for the selective use of pulmonary vasodilators but highlight the need for large prospective randomized control trials of pulmonary vasodilator therapies to fully assess the benefit of such therapies in Fontan-associated liver disease.